2011
DOI: 10.1016/s0140-6736(11)60967-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and medium-term health effects of 9/11

Abstract: The New York City terrorist attacks on Sept 11, 2001 (9/11), killed nearly 2800 people and thousands more had subsequent health problems. In this Review of health effects in the short and medium terms, strong evidence is provided for associations between experiencing or witnessing events related to 9/11 and post-traumatic stress disorder and respiratory illness, with a correlation between prolonged, intense exposure and increased overall illness and disability. Rescue and recovery workers, especially those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 89 publications
8
95
0
Order By: Relevance
“…Interestingly, apart from the direct effects on the enterocytes, the stressinduced increase of intestinal permeability is mediated via recruitment and activation of mast cells, eosinophils, macrophages and other mononuclear cells, and implicates both CRFR1 and CRF 2 receptors. 28 There is abundant literature supporting the link between life stress and the origin and clinical course of several human disorders, 179 however, the ultimate clinical relevance of stress-CRFmediated dysregulation of gastrointestinal permeability, remains at present mostly intuitive, with few exceptions. More work in this area is needed to confirm the findings.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, apart from the direct effects on the enterocytes, the stressinduced increase of intestinal permeability is mediated via recruitment and activation of mast cells, eosinophils, macrophages and other mononuclear cells, and implicates both CRFR1 and CRF 2 receptors. 28 There is abundant literature supporting the link between life stress and the origin and clinical course of several human disorders, 179 however, the ultimate clinical relevance of stress-CRFmediated dysregulation of gastrointestinal permeability, remains at present mostly intuitive, with few exceptions. More work in this area is needed to confirm the findings.…”
Section: Resultsmentioning
confidence: 99%
“…Quarterly incident birth-outcome data for the NYC area, consisting of Bronx, Kings, New York, Queens, and Richmond counties, were obtained from the New York City Department of Health and Mental Hygiene for 1990 through 2008 resulting in data for 76 quarters, 47 before the event and 29 after the event. We chose to study the metropolitan area as opposed to limiting it to Manhattan because there were studies on post-attacks birth outcomes that included the entire city and showed significant changes in outcomes 34 . Data were standardized as rates to control for population size differences.…”
Section: Introductionmentioning
confidence: 99%
“…Part of this resistance may be explained by the central neural circuitry responsible for the interaction between emotion and exacerbation of asthma (17); this circuitry is thought to be different from the inflammatory immune system. During or after catastrophic events, in patients influenced by disasters, the control of chronic diseases, such as hypertension or diabetes, worsens for a relatively long period (3,5,18). For instance, an increase in AMI incidence was reported after the Great Hanshin earthquake (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additional examples of devastating disasters include the attacks of September 11,2001 in New York, Virginia, and Pennsylvania. These attacks and subsequent rescue and recovery attempts also brought about various health problems and consequences to the USA, including the manifestation of mental health problems such as post-traumatic stress disorder or physical health problems such as respiratory diseases, gastro-esophageal symptoms, and cardiac complications (5,6). American residents living far from the aforementioned sites also presented with numerous stress symptoms, including the development of sleep disorders, difficulties in concentrating, and disturbing thoughts and/or memo Figure 1.…”
Section: Introductionmentioning
confidence: 99%